Posterolateral Lumbar Arthrodesis With and Without Interbody Arthrodesis for L4–L5 Degenerative Spondylolisthesis. Issue 12 (15th June 2015) - Gottschalk, Michael B.; Premkumar, Ajay; Sweeney, Kyle; Boden, Scott D.; Heller, John; Yoon, S. Tim; Rhee, John M.; Leckie, Steven K.; Braly, Brett; Simpson, Andrew K.; Lenehan, Eric
<x xml:space="preserve">Abstract</x> Study Design. Independent retrospective review of prospectively collected data, comparative cohort study. Objective. The objective of this study was to compare the clinical, radiographical, and cost/value of the addition of an interbody arthrodesis (IBA) to a posterolateral arthrodesis (PLA) in the surgical treatment of L4–L5 degenerative spondylolisthesis (DS). The authors hypothesized that the addition of IBA to PLA would produce added value while incurring minimal additional costs. Summary of Background Data. Many lumbar surgical advances have been made during the past several decades, yet there is a paucity of strong evidence-based validation, let alone comparative value analyses. The addition of an IBA to a PLA has become increasingly popular during the past 2 decades, yet the potential added value for the patient has not been carefully defined. Methods. Patients undergoing single-level arthrodesis for L4–L5 DS performed at our institution from 2004 to 2012 were identified. Exclusion criteria included multilevel arthrodesis, spinal stenosis requiring decompression at or above L2–L3, previous L4–L5 spinal fusion, spondylolisthesis of greater than 33% of the vertebral body, and use of minimally invasive surgery. Radiographical fusion status, epidemiological, surgical, and functional outcomes, and cost/value data were recorded or calculated. Results. A total of 179 patients with follow-up meeting inclusion criteria were identified: 68 with PLA alone and 111 with PLA + IBA. No statistical differences were noted in Oswestry Disability Index, 36-item Short-Form Health Survey scores, fusion rates, or cost/value at 6 months and at more than 3 years despite the PLA cohort being significantly older with more medical comorbidities. When length of stay was normalized across cohorts, the addition of an IBA increased hospital costs ranging from $577 to $5276, but this did not reach statistical significance. Conclusion. This single-center review of open surgical treatment of L4–L5 DS demonstrated that the addition of IBA to PLA added cost while producing equivalent results in fusion rates, Oswestry Disability Index, and 36-item Short-Form Health Survey scores when compared with PLA alone. Level of Evidence: 3